Back to the future: On the British liberal left's return to its origins. (1st March 2020) - Hall, Steve; Winlow, Simon
Why has the Labour Party in Britain been unable to take advantage of the historic opportunity presented by the global financial crisis to press its case for radical socio-economic reform? Why, despite more than a decade of Tory austerity and genuine signs of social crisis, does it find itself behind in the polls to a Conservative Party openly committed to shrinking the state and providing further tax cuts to the rich? In this short article, we reflect upon the history of the political left in Britain, and suggest that the liberalization of the left ‐ and the long-running marginalization of the working classes, their concerns and their real-world experiences ‐ reveals an underlying antagonism that is driving many voters supportive of interventionist economic policies but suspicious of the left's cultural agenda into the hands of the political right.